PELATIHAN GMP DAN HACCP BAGI POKLAHSAR RULE ATHALLAH DI KELURAHAN SUKAMARO, KECAMATAN TALANG KELAPA, KOTA PALEMBANG - Selly Ratna Sari; Guttifera Guttifera; Agung Riswandi (Universitas Mataram, 2023)
Efforts to efficiently utilize fishery products and economic value to extend the shelf life of fish are called fishery processing. Traditional markets and household scale industries still dominate the fishery processing industry. The processing and marketing group for fishery products in the Sukamoro sub-district is Poklahsar Rule Athallah. The application of technology that is capable of processing waste products and minimizing the remaining waste as well as the availability of raw materials both in quality and quantity and at relatively low prices must be supported by the development of appropriate processed fishery products. This activity aims to increase knowledge and skills in processing fishery products for Poklahsar Rule Athallah that meet Good Manufacturing Practice (GMP) and Hazard Analysis and Critical Control Points (HACCP) standards. The activity method used is lecture, pre-test and post-test. The results of the activities show that: 1). The understanding of Poklahsar members regarding the importance of joint efforts in one group is good. The implementation of the activities consisted of visits and meetings aimed at explaining in full the technological innovations of catfish-based fish processing, packaging, product labeling, and compiling simple business bookkeeping. 2). Craftsmen's knowledge of GMP and HACCP aspects is good. The results of the initial assessment showed that the average knowledge of the partner group on the development of a processing business made from catfish was 36.8%. While the average response value of the partner group after the implementation of the activity was 74.3%. This shows an increase in the knowledge of the partner group. In addition, the variation in the value of the partner group's response to the list of questions asked decreased from 5.12 to 4.68. The implementation of GMP and HACCP by members of the Rule Athallah Poklahsar could not be fully implemented due to various limitations.